Robotic neurosurgery: an active vision Guided robotic arm for endoscopic and Bone drilling maneuvers - Mohamed, Saufi Awang (2007)
Surgical robots have been appearing in the operating room over the past decade and neurosurgery was one of the pioneer in this area. The aims of this study were to create a program using V+ module and to design a suitable end effector capable of holding bone perforator and endoscope. In addition, the ability and accuracy of the robot perfonning bone drilling and endoscopic maneuvers were assessed. The study was divided into two parts which were bone drilling and endoscopic maneuvers. In bone drilling section, immediately after image processing, the coordinates of the target were detennined. The robotic arm (together with bone perforator) was simulated and driven to the target. The insertion force by the robot was placed at minimal as to allow the bone perforator to stop once it hit the plasticine. After a burr hole was made, the robot was instructed to move away from the target. A total of 30 burr holes were performed at 5 different positions (supine, sitting, right and left lateral, and prone). In endoscopic maneuver section, the robot was initiated to recognize the targeted burr hole. The robotic arm was simulated and driven to the targeted burr hole and placed the endoscope into the burr hole. On command, the robot was instructed to move forward (insertion) and outward. A total of ten burr holes were examined. In supine position, the accuracy was 1.0mm with the repeatability value ranged from 0.04mm to 0.17mm. Time taken to do burr holes was in the range of 13.1 to 14.3 seconds. In sitting position, the accuracy ranged from 0.1 mm to 1.0mm with the repeatability ranged from 0.1 Omm to 0.92 mm and time taken to perform burr holes ranged from 6.6 to 10.5 seconds. In left lateral position, the accuracy was 1.0mm with repeatability of 0.03 to 0.12 mm and in right lateral position, the accuracy ranged from 1.0mm to 2.0mm with repeatability of 0.10mm. Time taken to drill in left and right lateral was in the range of 14.0 to 15.4 seconds and 12.5 to 13.0 seconds respectively. In prone position, the accuracy ranged from 0.5mm to 1.0mm with repeatability of 0.08 to 0.31 nun and the time taken to drill was in the range of 9.0 seconds to 16.6 seconds. For endoscopic procedure, the accuracy ranged from 0.3mm to 1.0mm with repeatability of 0.31nun to 0.77mm and the endoscope was able to be inserted into all 10 burr holes. In summary, the present robotic arm has the ability to perform basic surgical procedures although there were some limitations. Further study is needed to refine the robotic system.